Different ways to integrate environmental values into car taxation policy - Bøgelund, Pia (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
Green car taxation – an introductory remark Perspectives on environmental policy making The concepts of sustainable development and ecological modernisation in comparison “Making transport pay its true costs” – throwing out the baby with the bathtub? A question of market failures Confronting the motorist with the true costs of transportation Calculating the monetary value of externalities Externality taxation in action Evaluating the “true costs” approach “Sustainable transport taxation” – loosing sight of a daily life? A question of ecological limits and distributional issues Changing fundamental structures of society The crucial role of participatory approaches in decision-making Inventing new decision-making instruments Evaluating the sustainability approach “Situated action in a global perspective” – suggesting a synthesis A characterisation of the two approaches Suggesting a synthesis